Extracellular vesicles derived from endothelial cells in hypoxia contribute to pulmonary artery smooth muscle cell proliferation in‐vitro and pulmonary hypertension in mice. (12th January 2022) - Chen, Tianji; Sun, Miranda R.; Zhou, Qiyuan; Guzman, Alyssa M.; Ramchandran, Ramaswamy; Chen, Jiwang; Ganesh, Balaji; Raj, J. Usha
Abstract: In the lung, communication between pulmonary vascular endothelial cells (PVEC) and pulmonary artery smooth muscle cells (PASMC) is essential for the maintenance of vascular homeostasis. In pulmonary hypertension (PH), the derangement in their cell–cell communication plays a major role in the pathogenesis of pulmonary vascular remodeling. In this study, we focused on the role of PVEC‐derived extracellular vesicles (EV), specifically their microRNA (miRNA, miR‐) cargo, in the regulation of PASMC proliferation and vascular remodeling in PH. We found that the amount of pro‐proliferative miR‐210‐3p was increased in PVEC‐derived EV in hypoxia (H‐EV), which contributes to the H‐EV‐induced proliferation of PASMC and the development of PH.